PENGARUH PEMBERIAN JUS BUAH PEPAYA TERHADAP PENURUNAN NYERI PADA PASIEN GASTRITIS DI RUMAH SAKIT HORAS INSANI TAHUN 2023 - Butar – Butar, Damenti; Rostime Hermayerni Simanulang (JOURNAL SAINS STUDENT RESEARCH, 2025)
Stomach pain due to inflammation, if not treated as early as possible or left untreated, will result in getting worse and ultimately stomach acid will cause sores (ulcers) known as gastric ulcers. The impact of ulcer disease can disrupt the patient's daily activities due to the emergence of various complaints such as heartburn, burning sensation, nausea, vomiting, weakness, lack of appetite, heartburn after eating, epigastric pain and other complaints. The aim of the research was to determine the effect of giving papaya juice on reducing pain in ulcer patients. Design a quasi-experimental research (quasi-experiment) with a research plan with an intervention group and a control group. The population in this study was all ulcer patients who visited Horas Insani Hospital in January – April 2023, totaling 56 people. Sampling was taken using a purposive sampling technique, that is, each subject was taken from a population that was chosen deliberately based on certain objectives and considerations. The sample size was 14 respondents in each group of 7 people. The instruments used were observation sheets and a Numerical Rating Scale questionnaire with the Man-Whitney hypothesis test because the data was not normally distributed. In conclusion, there is an effect of giving papaya juice on reducing pain in ulcer patients at Horas Insani Hospital. Year 2023 with p value = 0.002 < alpha 0.05. It is hoped that further suggestions can make this research a reference and point of reference for further research, as well as developing research related to stomach ulcers by providing other non-pharmacological therapies such as acupressure therapy, Benson relaxation, guided imagery, deep breathing relaxation and others.